Meningkatkan Kemampuan Menulis Teks Deskripsi Menggunakan Model Pembelajaran Think Talk Write (TTW) dengan Media Lingkungan Alam - Asih Riyanti; Siti Nurbaya (Indo-MathEdu Intellectuals Journal, 2023)
This research is Classroom Action Research (PTK) with the aim of improving the ability to write descriptive text using the Think Talk Write (TTW) learning model with natural environmental media. The natural environmental media used as objects of observation are those in the school environment. Subeyek, in this research, were 32 students at SMP 1 Pandak Bantul class VII. Data collection techniques in this research were interviews, tests and documentation. This research carried out two cycles, with the stages in each cycle being planning, action, Observation, and reflection. The results of student completion in the cognitive domain of cycle I were 50% and increased in cycle II to 84.37%; the affective domain in cycle I was 68.75%, increased in cycle II by 93.75%, Observation of student activities in cycle I was 60 .63 increased in cycle II by 90.71, Observation of teacher activities in cycle I was 68.35, increased in cycle II by 91.40. These results show that applying the TTW learning model with natural environment media can improve the ability to write descriptive text in class VII A students at SMP 1 Pandak Bantul.